Examining Cultural Identity Representation in Global Streaming Services and Its Influence on Audience Perception - Andrei Korneev; Gennady Lenevskt; Abdullayev Vugar (Medaad)
This study examines the role of global streaming platforms such as Netflix, Amazon Prime, and Disney+ in shaping cultural perspectives through the representation of different cultures in their content. The research aims to explore how cultural identity is expressed in different fields and fields, exploring the balance between realistic representations and the persistence of stereotypes. Primary objectives include examining cultural iconography patterns in selected shows and films and assessing their impact on intercultural understanding, empathy, and prejudice among audiences Research through content analysis of qualitatively, audience research, and focus groups reveal that while positive cues lead to greater appreciation and empathy for cultural diversity. The study offers recommendations for streaming services and content producers to promote a more nuanced and accurate portrayal of cultural diversity, as well as recommendations for future research on the role of AI in content production and strategies has enhanced intercultural understanding through global media and concludes.